Filsafat Eksklusivisme, Inklusivisme, dan Pluralisme dalam Dialog Antaragama: Studi Kasus pada Komunitas Tengger - Faiz; Zubaidi, Ahmad (Kartika: Jurnal Studi Keislaman, 2025)
The study of the philosophy of exclusivism, inclusivism, and pluralism in interreligious dialogue has become increasingly relevant in a globally connected and multicultural context. In Indonesia, particularly within the Tenggerese community in Sukapura, Probolinggo, religious differences are not only a challenge but also an integral part of the unique social dynamics. This research aims to explore how these philosophical concepts manifest in interreligious interactions within this community.The study employs a qualitative research method with a case study approach, involving participatory observation, in-depth interviews, and document analysis. The findings indicate that while tendencies toward exclusivism still exist among certain groups, significant efforts have been made to strengthen inclusivism and pluralism. Key factors such as traditional leadership, local cultural values, education, and collective experiences in maintaining social harmony play a crucial role in fostering more open and respectful interreligious dialogue.This research contributes by identifying best practices and challenges in managing religious diversity within the Tenggerese community. Furthermore, these findings are expected to serve as a reference for policymakers and practitioners in designing more effective and sustainable interreligious dialogue strategies while reinforcing social harmony based on local wisdom.